Quantitative analysis of Sildenafil citrat in the tablet (Viagra) by high-performance liquid chromatography (HPLC) method : Khóa luận tốt nghiệp Dược sĩ đại học / Phan Đoàn Thủy Tiên ; Nguyễn Hoàng Thảo My hướng dẫn - Phan, Đoàn Thủy Tiên
Phụ chú cuối tài liệu